Smooth Pursuit Study on an Eye-Control System for Continuous Variable Adjustment Tasks. Issue 1 (2nd January 2023) - Niu, Yafeng; Li, Xin; Yang, Wenjun; Xue, Chengqi; Peng, Ningyue; Jin, Tao
ABSTRACT: Smooth pursuit is a physiological phenomenon of human eyes, which can be used as eye-control interaction to avoid the "Midas" problem. This article describes the smooth pursuit properties of continuous variable tasks under Euclid's algorithm. Two experiments were conducted to investigate the effects of slider speed, initial position of "plus, " and variable value position on smooth pursuit interactions. The initial position and slider speed are combined in 12 combination forms, and the variable value positions are divided into 7 cases. Then, the optimal combination forms and variable value position case are derived. Experiment 1 divided the initial position into four levels of up, down, left and right and divided the slider speed into three levels of 1 deg/s, 2 deg/s, and 3 deg/s, concluding that the optimal combination of initial position and slider speed is that the speed is 2 deg/s and initial position is up. Experiment 2 was conducted on the basis of the conclusion obtained in experiment 1. The position of the variable value was divided into seven cases according to whether the left, center, and right of the smooth pursuit track the variable value appeared. The result showed that the position of the variable value in the center had the greatest influence on the pursuit efficiency. This research has an important value for the parameter set of smooth pursuit in the case of the Euclidean algorithm, it has great guiding significance for building smooth pursuit interaction in the context of the eye-control system.